Robin Osborne, The Transformation of Athens: Painted Pottery and the Creation of Classical Greece. - Mannack, Thomas (Journal of Greek Archaeology, 2022)
Robin Osborne, The Transformation of Athens: Painted Pottery and the Creation of Classical Greece. pp. 304, 20 col. + 80 b/w ills. Princeton: Princeton University Press 2018. ISBN 978-0-69117-767-0, hardcover £40.